2014
DOI: 10.1016/j.pain.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Sensory, psychological, and metabolic dysfunction in HIV-associated peripheral neuropathy: A cross-sectional deep profiling study

Abstract: SummaryStudy participants with HIV-associated sensory polyneuropathy (HIV-SN) had higher plasma triglyceride concentrations, depression, anxiety, catastrophizing scores, and prevalence of insomnia than HIV participants without HIV-SN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(97 citation statements)
references
References 67 publications
3
94
0
Order By: Relevance
“…Furthermore, by using the Neuropathic Pain Symptom Inventory it has been revealed that 42% of participants experiencing painful HIV-SN report symptoms of moderate and severe cold evoked pain, although this is not detected with sensory profiling [40]. Here, we have shown that indinavir-treated rats display increased thigmotaxis in the open field at the time of peak hindpaw mechanical hypersensitivity.…”
Section: Systemic Indinavir Induces a Minimal Spinal Microglial Respomentioning
confidence: 67%
See 2 more Smart Citations
“…Furthermore, by using the Neuropathic Pain Symptom Inventory it has been revealed that 42% of participants experiencing painful HIV-SN report symptoms of moderate and severe cold evoked pain, although this is not detected with sensory profiling [40]. Here, we have shown that indinavir-treated rats display increased thigmotaxis in the open field at the time of peak hindpaw mechanical hypersensitivity.…”
Section: Systemic Indinavir Induces a Minimal Spinal Microglial Respomentioning
confidence: 67%
“…Indeed, our recent study has shown that participants with painful HIV-SN have reduced quality of life, a higher incidence of insomnia, and increased depression, anxiety, and catastrophizing, when compared to participants without HIV-SN [40].…”
Section: Systemic Indinavir Induces a Minimal Spinal Microglial Respomentioning
confidence: 98%
See 1 more Smart Citation
“…The anticipated decline in HIV-SN with withdrawal of neurotoxic antiretroviral drugs is not yet evident, and this peripheral neuropathy still afflicts between 27% and 57% of people living with HIV of whom between 38% and 90% experience neuropathic pain. 8,11,21 Therefore, HIV-SN is one of the most frequent manifestations of HIV in people who are adequately treated with antiretroviral drugs. The burden of neuropathic pain in HIV-SN is further increased as it is peculiarly resistant to analgesic therapies that are effective in other painful neuropathies.…”
Section: The Burden Of "Hidden" Painmentioning
confidence: 99%
“…Cruickshank documented 58.6% of the 500 cases he assessed reported 'sharp', 'shooting' pain. 3,4,6,7 The pain symptom descriptors which feature in Peach's and other accounts are also prominent in modern day profiles of patients with painful neuropathies including HIV-associated sensory neuropathy 24 and diabetic neuropathy, which has been reported as 'distal, symmetrical, often associated with nocturnal exacerbations, and commonly described as prickling, deep aching, sharp like an electric shock, and burning' 25 ; corresponding with the descriptions given of BFS. For a grading of 'probable' neuropathic pain there is an additional requirement relating to sensory examination: 'sensory signs in the same neuroanatomically plausible distribution as pain'.…”
Section: Neuropathic Painmentioning
confidence: 90%